Stress generated by remote exams during the Covid-19 crisis and its relationship to physical activity: a cross-sectional study among medicine students (Research, Society and Development, 2022)
Background: Stress Generated by Remote Exams During the Covid-19 Crisis and its Relationship to Physical Activity: A Cross-Sectional Study Among Medicine Students. The study aimed to verify the autonomic alterations that occur in medical students in remote exams during the Covid-19 crisis and their relationship with physical activity. Study conducted with 22 medical students (9 women and 13 men) with a mean age of 19±1.5 years (18-24 years). The dependent variables were: changes in HRV. The independent variables of the study were physical activity (number of steps/day), age and sex. The results showed that the evaluation did not generate changes in the measured autonomic indicators, indicating that this model minimizes stress. It was evident that the greater the number of steps, the lower the stress index (r=-0.920). The other autonomic variables did not show a significant correlation with the number of steps. The remote assessment model used in the medical course during the Covid-19 crisis did not generate autonomic alterations indicative of stress in medical students. However, there was a low level of physical activity in this sample through the number of daily steps, on the other hand, those who had a higher number of steps had a lower stress rate.